Rev-induced modulation of Nef protein underlies temporal regulation of human immunodeficiency virus replication. - Ahmad, N (1989)
The replication of human immunodeficiency virus type 1 (HIV-1) requires the concerted action of two virus-encoded transactivator proteins, Tat and Rev, and is in turn moderated by the viral transcriptional repressor Nef. We show here that the phenotype of a Rev- HIV-1 provirus was nonreplicating and was distinguished by accumulation of Nef protein and reduced Tat function. Provirus defective in both the rev and nef genes (Rev-Nef-) was also nonreplicating but had normal Tat function. Trans-complementation of the Rev- mutant with Rev caused a decrease of both the steady-state level and the rate of synthesis of Nef. This was accompanied by enhanced synthesis of viral structural proteins. Rev induced even greater levels of virus production from the Rev-Nef- double mutant. In contrast, exogenous Rev did not augment virus production from wild-type provirus. Virus production from Rev- and Rev-Nef- mutants induced by Rev was repressed by exogenous Nef. The repression induced by Nef could not be reversed by exogenous Rev. The ability of Rev to modulate Nef expression solely from the provirus, and thereby relieve the Nef-mediated inhibition of transcription from the viral long terminal repeat, reveals a delicate balance of the functions of these two proteins that might underlie the switch between latency and reactivation.